The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s11064-012-0826-x
|View full text |Cite
|
Sign up to set email alerts
|

Huperzine A Ameliorates Cognitive Deficits and Oxidative Stress in the Hippocampus of Rats Exposed to Acute Hypobaric Hypoxia

Abstract: Acute exposure to high altitudes can cause neurological dysfunction due to decreased oxygen availability to the brain. In this study, the protective effects of Huperzine A on cognitive deficits along with oxidative and apoptotic damage, due to acute hypobaric hypoxia, were investigated in male Sprague-Dawley rats. Rats were exposed to simulated hypobaric hypoxia at 6,000 m in a specially fabricated animal decompression chamber while receiving daily Huperzine A orally at the dose of 0.05 or 0.1 mg/kg body weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 35 publications
6
19
0
Order By: Relevance
“…Our present investigation showed the remarkable elevation of caspase-3 activity in the cerebral cortex and hippocampus of diabetic rat brain and this effect was blocked by HupA treatment, implicating that HupA decreased neuronal death in a diabetic rat model. Consistently, it was previously illustrated that HupA attenuated caspase-dependent neuronal apoptosis in the hippocampus of rats during acute hypobaric hypoxia [31]. Moreover, HupA treatment also ameliorated serum deprivation-induced apoptosis via inhibiting mitochondria-dependent caspase-3 activity in cultures of rat cortical neurons [32].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Our present investigation showed the remarkable elevation of caspase-3 activity in the cerebral cortex and hippocampus of diabetic rat brain and this effect was blocked by HupA treatment, implicating that HupA decreased neuronal death in a diabetic rat model. Consistently, it was previously illustrated that HupA attenuated caspase-dependent neuronal apoptosis in the hippocampus of rats during acute hypobaric hypoxia [31]. Moreover, HupA treatment also ameliorated serum deprivation-induced apoptosis via inhibiting mitochondria-dependent caspase-3 activity in cultures of rat cortical neurons [32].…”
Section: Discussionsupporting
confidence: 66%
“…Animals in each experiment were randomly assigned to four groups: (1) control group (Con) ( n = 8), with normal rats that received saline intraperitoneally (physiological saline 0.1 mL/100 g); (2) vehicle group (DM) ( n = 8), the diabetic rats that received saline intraperitoneally (physiological saline 0.1 mL/100 g); (3,4) HupA groups (DM + HupA (0.05) and DM + HupA (0.1)) ( n = 8), diabetic rats treated with HupA at doses of 0.05 and 0.1 mg/kg, respectively. The dosage and dosing frequency of HupA were selected according to the previous reports [18,31]. HupA was freshly prepared by dissolving in the physical saline and injected intraperitoneally once a day.…”
Section: Methodsmentioning
confidence: 99%
“…Additional studies are necessary to reveal which components are responsible for antioxidative properties of the selected fractions, and to determine the exact mechanism of their antioxidative activity. It was previously suggested that HupA possesses potent antiapoptotic, neuroprotective and antioxidative properties [34,43,51,52,56]. Our study demonstrated that this alkaloid is not a direct scavenger of free radicals, and other mechanisms are responsible for its antioxidative potential.…”
Section: Discussionsupporting
confidence: 44%
“…This supplement has been shown to increase blood levels of ATP [22], increase exercise levels in sedentary individuals from a single dose [23], and enhance responses to chronic resistance training [24]. The supplement Huperzine has been shown to have positive effects on brain function, specifically decreasing cognitive deficits and oxidative stress in the rodent model after hypobaric hypoxia [25], and has been shown in conjunction with other supplements to enhance upper body strength endurance performance [6] and anaerobic sprint performance [26].…”
Section: Introductionmentioning
confidence: 99%